2009
DOI: 10.1104/pp.109.147660
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan-Derived Metabolites Are Required for Antifungal Defense in the Arabidopsis mlo2 Mutant

Abstract: Arabidopsis (Arabidopsis thaliana) genes MILDEW RESISTANCE LOCUS O2 (MLO2), MLO6, and MLO12 exhibit unequal genetic redundancy with respect to the modulation of defense responses against powdery mildew fungi and the control of developmental phenotypes such as premature leaf decay. We show that early chlorosis and necrosis of rosette leaves in mlo2 mlo6 mlo12 mutants reflects an authentic but untimely leaf senescence program. Comparative transcriptional profiling revealed that transcripts of several genes encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
160
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(178 citation statements)
references
References 84 publications
13
160
3
2
Order By: Relevance
“…We could not detect differences between the wild-type plant and the pmr4 mutant in the initial penetration success of the virulent powdery mildew Gc (Fig. 2G), thereby confirming data from Consonni et al (2010). Hence, callose deposition and the formation of a calloseencased penetration peg are not required for initial powdery mildew ingress and haustorium formation in a compatible interaction, which confirms previous reports regarding the development of fungal infection structures in the absence of callose formation (Jacobs et al, 2003).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We could not detect differences between the wild-type plant and the pmr4 mutant in the initial penetration success of the virulent powdery mildew Gc (Fig. 2G), thereby confirming data from Consonni et al (2010). Hence, callose deposition and the formation of a calloseencased penetration peg are not required for initial powdery mildew ingress and haustorium formation in a compatible interaction, which confirms previous reports regarding the development of fungal infection structures in the absence of callose formation (Jacobs et al, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…Whereas higher callose accumulation contributes to resistance against nectrophic fungal pathogens, such as Alternaria brassicicola and Plectosphaerella cucumerina (Ton and Mauch-Mani, 2004), recent results have suggested that callose deposition is irrelevant for plant resistance to adapted biotrophic powdery mildews (Consonni et al, 2010). However, our results proved that this assumption cannot be generalized.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…S6D). Camalexin, a major phytoalexin in A. thaliana, is known to be important for preinvasion resistance against powdery mildew, and atpad3-1, a camalexin-deficient mutant, is defective in the preinvasion resistance to both powdery mildew (47) and A. brassicicola (33). Second, A. brassicicola conidia germination was significantly reduced in the AtABCG34-overexpressing lines (Fig.…”
Section: Discussionmentioning
confidence: 99%